INDONESIA'S MINING PRODUCTS TRADE POLICY, DOWNSTREAMING AND CONTROVERSIAL INTERNATIONAL TRADE - Syahrudi; Abdul Azim Wahbi (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study investigates the impact of Indonesia’s trade policy on mining products, emphasizing the downstream processing strategy and its implications within international trade dynamics. Method: Using a qualitative approach combining policy analysis, literature review, and expert interviews, the research examines how Indonesia’s efforts to promote value addition through downstream processing have influenced trade relations and compliance with global trade norms. Results: The findings reveal that while the policy enhances domestic economic benefits and industrial competitiveness, it also generates tensions with several trading partners, sparking debates on trade fairness, market access, and the sovereignty of natural resource utilization. These controversies highlight the complex interplay between national economic interests and international trade obligations. Novelty: This study provides a comprehensive perspective on Indonesia’s downstream policy as a case of resource-based industrialization in a globalized economy, offering new insights into balancing national development goals with international trade commitments through cooperative and sustainable policy frameworks.